Pengaruh Penerapan E-Samsat dan Pajak Progresif terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Alif Muhammad Pratama; Marcelino Mustopa (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of the implementation of e-Samsat and progressive tax on motor vehicle taxpayer compliance at the Bandung City Samsat Office III Soekarno-Hatta. The background of this study is based on the fact that the level of taxpayer compliance has not yet reached an optimal level, despite the government’s efforts to implement technology-based tax services and fair taxation policies. This research employs a quantitative approach, with data collected through questionnaires distributed to motor vehicle taxpayers. The collected data were analyzed using statistical methods to examine both partial and simultaneous effects of the variables.The results indicate that the implementation of e-Samsat has a positive and significant effect on motor vehicle taxpayer compliance. The convenience, speed, and efficiency provided by the e-Samsat system enhance taxpayers’ awareness and discipline in fulfilling their tax obligations. Furthermore, progressive tax is also proven to have a positive effect on taxpayer compliance. The application of higher tax rates based on the number of vehicles owned encourages a sense of responsibility and fairness among taxpayers. Simultaneously, the implementation of e-Samsat and progressive tax positively influences motor vehicle taxpayer compliance and contributes to the optimization of regional tax revenue. Therefore, continuous improvement of the e-Samsat system, along with the fair and transparent implementation of progressive tax policies, is essential to sustainably increase taxpayer compliance and support local revenue growth.